Solid and fluid inclusions-data of colombian emeralds (1995)
Partial results of an ongoing research on the origin of the Emeralds of Colombia are presented. The deposits are confined along two belts on the eastern and western flanks of the "Cordillera Oriental" near Bogotá, Colombia.